Relationship Between Leadership and Commitment with Quality Performance on U-Th-REE Processing Pilot Plant Construction in BATAN - Nunik Madyaningarum; Mohammed Ali Berawi; Perdana Miraj (Pusat Teknologi Bahan Galian Nuklir - BATAN, 2018)
Management area of leadership and commitment in the quality management system is a mean to achieve successful functions, even more on construction industry. The objective of this research is to analyze the correlation between leadership and commitment focus management area and quality performance as indicated by rework. Research location is uranium (U), thorium (Th), and rare earth elements (REE) processing pilot plant construction area in Center for Nuclear Minerals Technology-BATAN. Primary data were collected from the 36 of 37 submitted questionnaires, and representing 97 % response rate. The research used descriptive analysis, which depends on the poll and the use of Statistical Package for the Social Sciences (SPSS) main program for data analysis. The relationship between leadership and commitment and quality performance was analyzed using spearman rank correlation coefficient. Findings of research provide guideline and alert to project managers or management of organization where leadership, commitment, infrastructure, and environmental work have moderate to strong correlation to rework level. The results further revealed that there is no relationship between responsibility and authority for the management system and organizational policy and construction quality performance. The research provides evidence, in fact to achieve the quality performance of a pilot plant construction must be concerned with leadership attribute, maintaining commitment and provide support resources on the whole project cycle. Area manajemen kepemimpinan dan komitmen dalam sistem manajemen mutu adalah sarana untuk mencapai keberhasilan suatu pekerjaan, terlebih pada industri konstruksi. Tujuan dari penelitian ini adalah untuk menganalisis hubungan antara area fokus manajemen kepemimpinan, komitmen, dan kinerja kualitas yang ditunjukkan dengan pengerjaan ulang (rework). Lokasi penelitian adalah area kontruksi pilot plant pengolahan uranium (U), torium (Th), dan unsur logam tanah jarang (LTJ) di Pusat Teknologi Bahan Galian Nuklir-BATAN. Data primer merupakan hasil 36 dari 37 kuisioner yang dikirimkan, dan mewakili tingkat respons 97 %. Penelitian ini menggunakan analisis deskriptif, yang bergantung pada polling dan menggunakan program utama Paket Statistik untuk Ilmu Pengetahuan Sosial (SPSS) untuk analisis data. Hubungan antara kepemimpinan dan komitmen dan kinerja kualitas dianalisis dengan menggunakan koefisien korelasi pemeringkatan spearman. Hasil penelitian memberikan panduan dan peringatan kepada manajer proyek atau manajemen organisasi bahwa kepemimpinan, komitmen, dan infrastruktur serta lingkungan kerja memiliki korelasi menengah hingga sangat kuat terhadap tingkat pengerjaan ulang. Hasil lainnya mengungkapkan bahwa tidak ada hubungan antara tanggung jawab dan wewenang sistem manajemen serta kebijakan organisasi dengan kinerja kualitas konstruksi. Penelitian ini memberikan bukti bahwa sebenarnya untuk mencapai kinerja kualitas konstruksi pilot plant harus memperhatikan atribut kepemimpinan, mempertahankan komitmen, dan memberikan sumber daya pendukung pada keseluruhan siklus proyek.